2021
DOI: 10.3389/fphys.2021.661429
|View full text |Cite
|
Sign up to set email alerts
|

A Heart Failure-Associated SCN5A Splice Variant Leads to a Reduction in Sodium Current Through Coupled-Gating With the Wild-Type Channel

Abstract: Nav1.5, encoded by the gene SCN5A, is the predominant voltage-gated sodium channel expressed in the heart. It initiates the cardiac action potential and thus is crucial for normal heart rhythm and function. Dysfunctions in Nav1.5 have been involved in multiple congenital or acquired cardiac pathological conditions such as Brugada syndrome (BrS), Long QT Syndrome Type 3, and heart failure (HF), all of which can lead to sudden cardiac death (SCD) – one of the leading causes of death worldwide. Our lab has previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…We have also evidenced that Na v 1.5 α-subunits form dimers through an interaction site located in the domain I-II linker, and that Na v 1.5 channels not only interact but also gate as dimers [10]. More recently, we and others reported that dominant negative suppression exerted by Na v 1.5 mutants could also be caused by impairing the WT gating probability, a mechanism resulting from the coupled gating of Na v channel α-subunits [6,8,11]. Altogether, these observations led us to examine the capacity of Na + channels to transcomplement trafficking or gating-deficient mutant channels to rescue I Na .…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…We have also evidenced that Na v 1.5 α-subunits form dimers through an interaction site located in the domain I-II linker, and that Na v 1.5 channels not only interact but also gate as dimers [10]. More recently, we and others reported that dominant negative suppression exerted by Na v 1.5 mutants could also be caused by impairing the WT gating probability, a mechanism resulting from the coupled gating of Na v channel α-subunits [6,8,11]. Altogether, these observations led us to examine the capacity of Na + channels to transcomplement trafficking or gating-deficient mutant channels to rescue I Na .…”
Section: Introductionmentioning
confidence: 60%
“…Unlike potassium channel genes, which encode one fourth of tetramers constituting functional channels, Na v 1.5 channels were thought to be structured as monomers, since the gene encodes the entire 4domain channel α-subunit. It was thus unexpected to report Na v 1.5 mutants with a dominant-negative effect on wildtype (WT) channels, i.e., a decrease of I Na exceeding the 50% of current density expected in case of haploinsufficiency observed when coexpressing some mutants with WT channels in a 1:1 ratio to mimic patient heterozygosity, as we and others did [2][3][4][5][6][7][8][9]. Furthermore, we demonstrated that Na v 1.5 α-subunits could interact with each other and that a trafficking-efficient mutant channel was able to drive a trafficking-deficient one to the surface membrane [3].…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…The multifunctional regulatory protein 14-3-3 has been reported to be critical for mediating Na V 1.5 dimerization, and an operative mechanism in select cases of the dominant negative effect (8). Indeed, difopein, an inhibitor of 14-3-3, (37) was shown to restore WT activity when co-expressed with dominant negative variants (8, 38). While targeting 14-3-3 may not be an appropriate therapeutic strategy given its role in myriad cellular processes, alternative mechanisms to promote selective degradation of aberrant channels and preserve WT function remain highly desirable.…”
Section: Discussionmentioning
confidence: 99%